PERAN MEDIA ONLINE TERHADAP FASHION HIJAB PADA MAHASISWI PRODI PENDIDIKAN IPS, FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA - Cut Dien Nourwahida (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
This study looks at the role of online media on the influence of fashion on female students. Syarif Hidayatullah State Islamic University Jakarta. This research was conducted with the aim to know the role of online media on the influence of student fashion IPS, State Islamic University Syarif Hidayatullah Jakarta.This study uses a qualitative approach with descriptive method of analysis, which is a way used to investigate and solve problems that occur in the present moment.Fashion Hijab is an important thing for IPS educational students, because with the hijab fashion makes the student becomes more stylish, beautiful and not outdated. Online media is very instrumental to fashion hijab for IPS education student, that is to add insight or information about fashion hijab, add the reference of hijab fashion and facilitate student of IPS Education in creation of hijab in everyday as well as with the online media, photographs uploaded in online media became the student reference used.